Landmark Identification of Pekanbaru - Huda, Samani -; Tela, I Nengah; Haryani, Haryani; Marison, Artian Ferry; Kusumah, Dadang Puja (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
Landmarks play a vital role in shaping the city’s image as orientation markers and visual identity elements. Pekanbaru, the capital of Riau Province, has experienced rapid development that produced many iconic buildings, yet systematic studies based on public perception remain limited. This research aims to identify the main landmarks of Pekanbaru City and analyze the visual characteristics influencing their legibility. A mixed-method approach was applied through field observation, visual documentation, and a questionnaire survey involving 150 purposively selected respondents. Descriptive and statistical analyses using SmartPLS were conducted to examine relationships among visual perception variables (singularity, location, uniqueness, memorable) and landmark recognition. The findings reveal that An-Nur Grand Mosque, Soeman HS Library, and the Riau Governor’s Office are the most recognized landmarks. Location and memorable factors have significant positive effects, while uniqueness shows a negative influence. The study emphasizes that enhancing landmark design and spatial arrangement strengthens urban navigation and visual identity in Pekanbaru.